Effect of anion on water-in-salt/solid interfacial structures investigated by atomic force microscopy. (1st September 2022) - Tsuyoshi, Jumpei; Bao, Yifan; Ichii, Takashi; Utsunomiya, Toru; Sugimura, Hiroyuki
Abstract: Water-in-salt (WiS), which contains salt with a high salt concentration (>5 mol kg −1 ), is attractive for novel electrolytes in electrochemical applications such as lithium-ion batteries and electrochemical deposition because of its high electrochemical stability. Structural analysis on the WiS/solid interfaces would be beneficial for understanding these processes. In this study, we investigated interfacial solvation structures of WiSs by frequency modulation atomic force microscopy utilizing a quartz tuning fork sensor. Two types of WiSs, a lithium bis(trifluoromethanesulfonyl) imide (LiTFSI)-WiS and a LiCl-WiS, were prepared. We found that the interfacial solvation structures of the WiSs on mica surfaces were quite different by using a 2D frequency shift mapping technique. We discussed the differences in their interfacial solvation structures by comparing their bulk solution properties measured by Raman spectroscopy.